2022
DOI: 10.1021/acs.iecr.1c04288
|View full text |Cite
|
Sign up to set email alerts
|

Newtonian and Non-Newtonian Viscosity of Waxy Crude Oils and Condensates: A Noncompositional Model

Abstract: Waxy crude oils and condensates exhibit Newtonian behavior above the wax appearance temperature (WAT) and non-Newtonian below it. This research shows that, at temperatures slightly below the WAT, they behave close to a Bingham plastic. With more temperature reduction, the behavior approximately alters to a shear thinning fluid with yield stress while more shear thinning intensity is observed as the temperature continues to decrease. In accordance with this behavior, a viscosity model generalized by the Particl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 72 publications
(184 reference statements)
0
3
0
Order By: Relevance
“…The apparent viscosity vs shear rate of PVA pellets with different water contents at 150 °C is shown in Figure . With the increase of shear rate, the apparent viscosity of all samples consistently decreased in an almost linear fashion, suggesting that the melt of PVA pellets exhibited the characteristic shear thinning behavior of the pseudoplastic fluid . More water in the PVA matrix led to a decrease in apparent viscosity, indicating that PVA with higher water content encountered less resistance during extrusion.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…The apparent viscosity vs shear rate of PVA pellets with different water contents at 150 °C is shown in Figure . With the increase of shear rate, the apparent viscosity of all samples consistently decreased in an almost linear fashion, suggesting that the melt of PVA pellets exhibited the characteristic shear thinning behavior of the pseudoplastic fluid . More water in the PVA matrix led to a decrease in apparent viscosity, indicating that PVA with higher water content encountered less resistance during extrusion.…”
Section: Resultsmentioning
confidence: 93%
“…With the increase of shear rate, the apparent viscosity of all samples consistently decreased in an almost linear fashion, suggesting that the melt of PVA pellets exhibited the characteristic shear thinning behavior of the pseudoplastic fluid. 50 More water in the PVA matrix led to a decrease in apparent viscosity, indicating that PVA with higher water content encountered less resistance during extrusion. It is worth noting that as the water content increased, the slope of the curve became flatter, displaying the lower sensitivity of the melt with more water to the shear rate.…”
Section: Thermal Analysis Of Pva Pelletsmentioning
confidence: 99%
“…In order to analyze the rheological mechanism of waxy crude oil emulsion comprehensively, numerous scholars have conducted investigations on various conditions including viscosity temperature, 2 thixotropic properties, 3 yield stress, 4 and viscoelastic characteristics. 5 It has been observed that these properties are closely associated with shear rate, 6,7 shear time, 8 water content, 9,10 temperature, 11–15 as well as colloids and asphaltene content. 16,17 With the continuous advancement of research and technological innovation, a growing number of researchers have redirected their focus towards investigating the evolutionary process of microstructure.…”
Section: Introductionmentioning
confidence: 99%